Interictal Cognitive Performance in Children and Adolescents With Primary Headache: A Narrative Review - Tarantino, Samuela; Proietti Checchi, Martina; Papetti, Laura; Ursitti, Fabiana; Sforza, Giorgia; Ferilli, Michela Ada Noris; Moavero, Romina; Monte, Gabriele; Capitello, Teresa Grimaldi; Vigevano, Federico; Valeriani, Massimiliano (Frontiers in Neurology, 2022)
Migraine is a very common and disabling disease. The burden of pain and recurrent attacks may lead to a poor quality of life, anxiety and depression. An increased risk of low functioning and curricular performances in young patients with primary headache has been described. The mechanisms underlying the relationship between migraine and poor school achievement may be various and could be a reflection of weak cognitive skills. Data concerning the cognitive functioning in the free pain interval in pediatric age are under-investigated and results are far from conclusive. The present review article suggests that, though considered a benign disease, pediatric migraine may be associated to altered neuropsychological functioning in the interictal phase. Although children and adolescents with migraine generally have a normal intelligence, they may show a not homogeneous cognitive profile, characterized by possible difficulties in verbal skills, in particular comprehension abilities. Pediatric primary headache may present altered neuropsychological functioning involving attentional resources, processing speed and memory, particularly verbal memory. Given the impact that this disease can have on school performance and the tendency to persist from childhood to adulthood, a cognitive screening in young patients affected by primary headache is pivotal. Additional neuropsychological research using more homogenous methods is needed.